Separation of electrons and protons in the GAMMA-400 gamma-ray telescope. Issue 7 (1st October 2015) - Leonov, A.A.; Galper, A.M.; Bonvicini, V.; Topchiev, N.P.; Adriaini, O.; Aptekar, R.L.; Arkhangelskaja, I.V.; Arkhangelskiy, A.I.; Bergstrom, L.; Berti, E.; Bigongiari, G.; Bobkov, S.G.; et al.
Abstract The GAMMA-400 telescope will measure the fluxes of gamma rays and cosmic-ray electrons and positrons in the energy range from 100 MeV to several TeV. These measurements will allow it to achieve the following scientific objectives: search for signatures of dark matter, investigation of gamma-ray point-like and extended sources, study of the energy spectrum of the Galactic and extragalactic diffuse emission, study of gamma-ray bursts and gamma-ray emission from the active Sun, together with high-precision measurements of the high-energy electrons and positrons spectra, protons and nuclei up to the knee. The bulk of cosmic rays are protons and helium nuclei, whereas the lepton component in the total flux is ∼10−3 at high energy. In the present paper, the simulated capability of the GAMMA-400 telescope to distinguish electrons and positrons from protons in cosmic rays is addressed. The individual contribution to the proton rejection from each detector system of GAMMA-400 is studied separately. The use of the combined information from all detectors allows us to reach a proton rejection of the order of ∼4 × 105 for vertical incident particles and ∼3 × 105 for particles with initial inclination of 30° in the electron energy range from 50 GeV to 1 TeV.